Chapter: 'Future Research Directions for Innovating Pedagogy' from book: Adaptive and Adaptable Learning:11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Mike Sharples (Lecture Notes in Computer Science, 2016)
A series of reports on Innovating Pedagogy were launched in 2012 to look at the trends that show how practitioners may engage in innovation in pedagogy. This paper looks at the latest set of trends, and highlights four 2015 trends that seem particularly rich for researchers to explore in the next five years.